Effectiveness of Early Intervention on Language Development in Children with Hearing Loss: A Systematic Review - Sutanto, Alfiani Vivi; Sudarman, Sudarman (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Hearing loss in children is one of the main causes of delayed language development, which affects cognitive, social, and academic domains. Early interventions such as hearing aids (HA), cochlear implants (CI), and speech therapy have been developed to minimize these impacts. Objectives: This study aims to review the effectiveness of early intervention on language development in children with hearing loss using a systematic review approach. Methods: Literature searches were conducted through PubMed, Scopus, ScienceDirect, CINAHL, and Google Scholar databases, with inclusion criteria focusing on children aged 0–6 years who received intervention before six months of age. Results: Seven studies met the eligibility criteria and were included in the synthesis. The results indicate that children who received intervention before six months demonstrated significantly better receptive and expressive language outcomes compared to those who were treated later. Factors such as family involvement, consistent device use, and the application of auditory-verbal therapy contributed substantially to successful intervention outcomes. Conversely, delayed diagnosis and limited service accessibility remain major barriers in developing countries. Conclusion: early intervention is proven effective in enhancing language development among children with hearing loss; therefore, early screening and timely therapy should be prioritized within pediatric healthcare services. Keywords: Early intervention, Hearing loss, Language development, Effectiveness